A Temperature‐Responsive Electrolyte Endowing Superior Safety Characteristic of Lithium Metal Batteries. Issue 6 (19th December 2019) - Zhou, Qian; Dong, Shanmu; Lv, Zhaolin; Xu, Gaojie; Huang, Lang; Wang, Qinglei; Cui, Zili; Cui, Guanglei
Abstract: Lithium metal batteries (LMBs) have attracted wide attention due to their high energy density. However, flammable organic carbonate electrolytes are associated with severe parasitic reactions and huge safety hazards for LMBs. Herein, a smart temperature‐responsive electrolyte is presented that demonstrates two distinct polymerization behaviors in LMBs. Through an anionic polymerization triggered by lithium metal, this electrolyte forms a favorable polymer protection layer on lithium anodes at ambient temperature, leading to a reversible Li plating/stripping behavior over 2000 h, and dendrite‐free morphology even under a current density of 10 mA cm −2 . On suffering from thermal abuse, this electrolyte can be rapidly transformed from liquid into solid by a thermal free radical polymerization, thus realizing significant improvements in safety performance without internal short‐circuit failures thus achieving safe operation even at a temperature of 150 °C. It is noted that no thermal runway occurs even at an extremely high temperature of 280 °C. It is believed that this study not only offers new valuable insights in interfacial chemistry of electrolytes, but also opens up new avenue to develop safe LMBs. Abstract : A temperature‐responsive electrolyte with two distinct polymerization behaviors is designed to improve the safety of lithium metal batteries. This smart liquid electrolyte can be rapidly transformed into a solid state and reinvent itself under thermal abuse, just like the rebirth of phoenix, which exhibits outstanding safety performance and give a new life to lithium metal battery.